BERT-GAT: Hierarchical Feature Interaction with Dynamic Multi-Hop Attention for Unstructured Data Management - Li, Shuqing; Wang, Jinghua; Liu, Chang; Xiong, Haochen; Cheng, Liujie (Informatica, 2025)
At present, unstructured data is growing rapidly, but traditional methods struggle to capture both deep semantics and complex structural relationships. This paper proposes a BERT-GAT fusion architecture to address this gap. We use BERT-base for semantic encoding (capturing contextual features) and a standard GAT with 2 layers and 8 attention heads for structural modeling. The architecture integrates a hierarchical feature interaction layer (fusing multi-granularity semantics) and a dynamic multi-hop attention module (modeling long-distance dependencies). Experiments are conducted on a proprietary dataset of 999,000 unstructured texts from a power grid management system (training/test split: 8:2). Evaluation metrics include accuracy (P), recall (R), and F1-score, with baselines including CNN, BERT-base, and GAT alone. Results show the fusion architecture achieves 87.0% accuracy (23.5% higher than CNN, p<0.01), 45.67% recall (12 percentage points higher than BERT-base, p<0.05), and an F1-score of 0.75 higher than BERT alone. The average retrieval response time is 56.2±3.1 seconds (on dual NVIDIA A100 GPUs). This work provides a robust framework for unstructured data management by integrating semantic and structural modeling.